First order chemical reaction effects on exponentially accelerated vertical plate with variable mass diffusion in the presence of thermal radiation - Muthucumaraswamy, Rajamanickam; Lakshmi, C. Santhana (Zielona Góra: Uniwersytet Zielonogórski)
Effects of transfer of mass and free convection on the flow field of an incompressible viscous fluid past an exponentially accelerated vertical plate with variable surface temperature and mass diffusion are studied. Results for velocity, concentration, temperature are obtained by solving governing equations using the Laplace transform technique. It is observed that the velocity increases with decreasing values of the chemical reaction parameter or radiation parameter. But the trend is just reversed with respect to the time parameter. The skin friction is also studied.
Keywords: exponential; radiation; isothermal; vertical plate; heat transfer; mass transfer